2019
DOI: 10.1002/jcb.29215
|View full text |Cite
|
Sign up to set email alerts
|

Association and in silico investigations of miR‐302c insertion/deletion variant as a novel biomarker with susceptibility to gastric cancer

Abstract: Gastric cancer (GC) is the fifth most prevalent malignant tumor and the third most frequent cause of cancer mortality worldwide. rs199971565 is an insertion/deletion (INDEL) located in microRNA‐302c (miR‐302c) seed site, which may affect its function and biogenesis. There is no genetic association study investigating this INDEL with any disease till now. Thus, the current study was conducted to investigate the association of rs199971565 with susceptibility to GC in an Iranian population. In addition, in silico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Gene insertions and deletions are common, which will cause gene polymorphisms, affect gene functions and biological characteristics, and are often associated with the occurrence of cancer. [ 27 , 28 ] Some studies showed that GAS5 polymorphisms may reduce cancer risk. Tang et al [ 14 ] showed that the rs145204276 del allele induced promoter activity by binding to transcriptional factor specificity protein 1, thereby preventing the development of breast cancer and ultimately leading to higher expression levels of GAS5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene insertions and deletions are common, which will cause gene polymorphisms, affect gene functions and biological characteristics, and are often associated with the occurrence of cancer. [ 27 , 28 ] Some studies showed that GAS5 polymorphisms may reduce cancer risk. Tang et al [ 14 ] showed that the rs145204276 del allele induced promoter activity by binding to transcriptional factor specificity protein 1, thereby preventing the development of breast cancer and ultimately leading to higher expression levels of GAS5.…”
Section: Discussionmentioning
confidence: 99%
“…Gene insertions and deletions are common, which will cause gene polymorphisms, affect gene functions and biological characteristics, and are often associated with the occurrence of cancer [27,28] . Some studies showed that GAS5 polymorphisms may reduce cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Rahimi et al explored potential hairpin structures and differentiated real miRNA precursors from pseudo ones through the application of RNAfold, allowing the selection of hsa-miR-B43 as one of the best candidates which might have a potential metastasis-related function in breast cancer [50]. RNAfold and RNAstructure were also able to demonstrate that the free energy of miR-302c stem-loop structure was more negative in the presence of the wildtype compared to the variant allele, leading to the suggestion that rs199971565 SNP is a novel INDEL biomarker located in the seed site of miR-302c, which may have crucial roles in the susceptibility to gastric cancer [51]. HMM is a probabilistic model and belongs to methods able to find similarity between sequences.…”
Section: Computational Biology Predictionmentioning
confidence: 97%